2014
DOI: 10.1177/1464420714535386
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of springback in anisotropic sheet metals: The effect of orientation and friction

Abstract: In this paper, springback of anisotropic sheet based on the modified form of the asymmetric non-quadratic yield function (YLD96) for plane stress conditions due to Barlat et al. (Yield function development for aluminium alloy sheets. J Mech Phys Solids 1997; 45: 1727–1763), suitable for describing mixed (isotropic and kinematic) hardening in aluminium alloy sheets under the Bauschinger Effect was compared with the results of tests. Simulation of uniaxial tensile and cyclic tests including both nonlinear isotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…anelastic recovery) would result in inaccurate estimation of springback, as this has not often been considered in existing studies on springback reported in the literature [1,8,9,11] for different sample orientations. These results are in agreement with a number of studies evaluated the effects of anisotropic mechanical properties on springback [7,[28][29][30]. Therefore, it is imperative to consider materials anisotropic behaviour, to estimate springback accurately.…”
Section: Springback Characterisationsupporting
confidence: 90%
See 1 more Smart Citation
“…anelastic recovery) would result in inaccurate estimation of springback, as this has not often been considered in existing studies on springback reported in the literature [1,8,9,11] for different sample orientations. These results are in agreement with a number of studies evaluated the effects of anisotropic mechanical properties on springback [7,[28][29][30]. Therefore, it is imperative to consider materials anisotropic behaviour, to estimate springback accurately.…”
Section: Springback Characterisationsupporting
confidence: 90%
“…Few studies have attempted to take the anisotropic mechanical properties into an account when estimating springback [7,[28][29][30]. It was concluded that the springback magnitude was dependent on the orientation of the investigated sample with respect to the rolling direction of the original sheet.…”
Section: Introductionmentioning
confidence: 99%